Web-Based Diabetic Ulcer Screening Class - Diah Merdekawati; Rasyidah AZ; Ani Astuti; Yuli Astuti; Zuldevina Karlin (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2026)
People with diabetes mellitus (DM) are at risk of developing ulcers. Simpang Kawat Health Center in Jambi City experiences an increase in the number of DM patients every year. Prevention efforts can be done through screening. In line with the times, screening can be done easily and quickly without visiting health services, namely through a web-based application. Participants in this activity were 15 elderly posyandu cadres in the Simpang Kawat Health Center Work Area. Participants were given training in diabetic ulcer screening and access to the provided smart screening application. There was an increase in participant knowledge after being given training (p value = 0.000). Training can increase participants' knowledge in conducting web-based diabetic ulcer screening.